Clean and low-cost synthesis of high purity beta-silicon carbide with carbon fiber production residual and a sandstone. (20th November 2019) - Sun, Kaidi; Wang, Tongtong; Chen, Zhe; Lu, Wenyang; He, Xin; Gong, Weibo; Tang, Mingchen; Liu, Fangjing; Huang, Zaixing; Tang, Jinke; Chien, TeYu; Tan, Gang; et al.
Abstract: The U.S. Department of Energy has initiated conversion of coal to solid materials, which can improve the coal-derived high-value product chain and decrease coal utilization related carbon dioxide emission. An integrated coal utilization technology was developed to respond to Department of Energy's call, which is extracting the molecules with desired molecular weight and structure in coal for carbon fiber production, then using carbon-rich residual from carbon fiber precursor extraction as carbon source to produce beta-silicon carbide. For the first time beta-silicon carbide is synthesized from carbon fiber production residual and a sandstone. The synthesized beta-silicon carbide was characterized with multiple analytical techniques. The product exhibits good properties with its purity, density, and Vickers hardness reach the requirements of commercial silicon carbide. Specifically, the purity of the beta-silicon carbide obtained with the two inexpensive raw materials under argon atmosphere at 1600 °C reaches as high as 98%. It is the first time that the furnace-MS system was applied to analyze the gaseous products in coal-based beta-silicon carbide synthesis process. Also, a possible synthesis mechanism was proposed and confirmed with experimental results. The research further analyzed the environmental impact and proposed the possibility that the liquid wastes/byproducts generated during raw material treatment process can be recycled and efficiently reused as coagulants or desiccants when the developed beta-silicon carbide synthesis process is applied in industry. This study provides a clean and low-cost approach for reusing waste residual from coal-based carbon fiber production and sandstone powder. Graphical abstract: Image 1 Highlights: β-SiC is synthesized from coal-based carbon fiber precursor extraction residual/waste. Producing both carbon fiber and β-SiC from coal can effectively control CO2 emission. A new β-SiC production mechanism is proposed and confirmed with experiments.